Timely Actions in the Presence of Uncertain Timeliness - Casimiro, António (2009)
Distributed systems are widely used today, mostly supported by the Internet. In consequence, there is an increasing demand for networked applications and services traditionally available only in specific, controlled settings. This includes many real-time applications, mostly mission-critical, such as multimedia rendering or on-line transaction processing. But the Internet, as well as many other small-scale computing environments, is open in nature and hence unpredictable. Therefore, to construct such applications in a dependable way, system architects have to face, among others, the challenge of reconciling the need for timeliness with the unpredictable nature of the environment. This thesis contributes with a new paradigm to address the problem of doing timely actions in the presence of uncertain timeliness. It proposes the Timely Computing Base (TCB) distributed system model to handle partial synchrony in a generic way and describes a set of fundamental services to be provided by TCB local modules. It also proposes some protocols that may be used to construct these services. The ability to construct dependable applications requires a comprehensive treatment of the fundamental cause of misbehavior due to lack of synchronism: timing failures. The thesis introduces generic properties that dictate the correctness of applications and explains, for several classes of applications, the methodology that must be followed for the latter to secure these properties and achieve their dependability objectives with the help of the TCB. Finally, the feasibility of the proposed model is evaluated